Productivity gains of DevOps adoption: a case study - Silva, Miguel Ângelo Rodrigues da (2019)
The main purpose of this research is to assess the productivity gains from the merge of two traditional IT teams: Development and Operations into a single DevOps team implementing 6 DevOps capabilities This research was conducted using the Case Study methodology, the author goes through the existing DevOps literature to better frame this research and the reader. To answer the formulated research question the author analyzed the team capacity planning divided by tasks type before and after a DevOps transition and interviewed 5 senior team members to collect their opinion about this transition. Observation was also part of this research and it was done by the author. The main objective is to analyze if there were productivity gains of that team after making the transition to a DevOps approach. The main contribution of this research is to analyze and extract results of the application of the DevOps capabilities in a real-world scenario where two teams are merged into a single DevOps team. As an example, we can observe that the operational work of the team decrease from 50% to 20%